Impact of Combination Treatments of Modified Atmosphere Packaging and Refrigeration on the Status of Antioxidants in Highly Perishable Strawberries. Issue 2 (10th March 2015) - Bhat, Rajeev; Stamminger, Rainer
Abstract: Strawberry fruits are highly appreciated for their distinctive aroma, mouthfeel and exceptional organoleptic properties. However, owing to their perishable nature, preservation and extension of shelf life of strawberries has been a major challenge. In this study, for the first time, combination effects of modified atmosphere packaging (combination of N2 and CO2 with 1% O2 ) and refrigeration (0, 5 and 10C, with 25C as control) on antioxidant activity and level of antioxidant compounds were evaluated. Encouraging results were obtained, which were all depended on the packaging, temperature used and storage days. Practical Applications: The present research work is expected to add database to the existing knowledge on various challenges incurred for safe preservation and shelf life extension of strawberries. Depending on the requirements, it is envisaged that the information generated in this study will be of practical help to comprehend the effectiveness of employing combination treatments of modified atmosphere packaging and cold storage treatments on handling freshly harvested strawberries and can be explored commercially for preservation purposes, provided more standardization is undertaken.